Reversibly cross-linked poly(ethylene glycol)–poly(amino acid)s copolymer micelles: a promising approach to overcome the extracellular stability versus intracellular drug release challenge. Issue 26 (22nd March 2015) - Li, Yuling; Wang, Sai; Zhu, Dandan; Shen, Yuling; Du, Baixiang; Liu, Xiaojun; Zheng, Yuanlin
<x xml:space="preserve">Abstract</x> Reversibly shell cross-linked micelles based on a lipoic acid (LA) decorated triblock copolymer poly(ethylene glycol)-b-poly(γ-benzyl-l-glutamate)-b-poly(l-phenylalanine) have been developed for efficient intracellular delivery of DOX.